A rare cause of facial nerve palsy in a young infant: Kawasaki disease - Orgun, Ali; Karagöl, Cüneyt; Pamuk, Utku; Gürsu, Hazım Alper; Çetin, İlker (The Turkish Journal of Pediatrics, 2018)
Kawasaki disease (KD) is a vasculitis in which the most common complication is development of coronary aneurysms. Neurological complications rarely occur in KD patients such as facial nerve palsy (FNP). FNP associated with KD may indicate increased risk of coronary artery aneurysm. Infants with facial nerve paralysis and unexplained-prolonged febrile period should be evaluated with echocardiography. Here in, we present a 4-month-old female with FNP and unexplained fever who was diagnosed KD due to echocardiographic findings.
Keywords: coronary aneurysm; echocardiography; facial palsy